Unequal Treatment or Uneven Consequence: A Content Analysis of Americans with Disabilities Act Title I Disparate Impact Cases from 1992 – 2012 - Johnston, Sara P. (Disability Studies Quarterly, 2015)
This study identified patterns and trends of litigation in all reported U.S. Appellate Court ADA cases charged under the theory of disparate impact (unintentional discrimination) from 1992 through 2012. The results produced four themes: accommodation(s); workplace culture, norms, and policies; judicial process; and policy space; and three relationships: gap-filling, weighing and balancing, and maintaining status quo versus effecting social change. The results may provide information about the types of workplace policies and procedures that are most frequently litigated. Disability scholars, advocates, and practitioners may be able to use the information to develop education and outreach strategies for employers on best practices for hiring, accommodating, and promoting employees with disabilities. The results may also be used to educate and inform advocates about the process of litigation. A greater understanding of how judges make decisions in a subset of ADA cases may increase employees with disabilities' ability to self-advocate in the workplace.